DEVELOPING READING ASSESSMENT INSTRUMENT FOR INTERMEDIATE EFL LEARNERS: AZWAR MODEL - Masitoh, Fitriatul; Fitriyah, Ima; Mukminatien, Nur (English Review: Journal of English Education, 2023)
The study was inspired by the fact that teachers of an intermediate English reading course employed a pre-made reading instrument particularly tests obtained from the internet, the TOEFL, or a textbook without consulting the learning objectives. Therefore, they cannot meet the demand of the teaching and learning objectives and the classroom-based assessment that should be tailored to the unique circumstances of the course. The objective of this study is to create intermediate reading comprehension test items for EFL students that adhere to the "good test" criterion generated utilizing the Azwar Model (1996). Second-semester students of English Language department in one of institutions in Kediri, Indonesia were meant to take a reading test using this instrument. The results of the try-out from 75 EFL students from the same level demonstrates that the test met the requirements of being valid, reliable, and practical, had moderate difficulty level, good discrimination levels as the most, and 73 functional distractors of the total. Meanwhile, five-invalid test items are not going to be included to be utilized in assessing EFL students’ reading comprehension. Intermediate reading course lecturers could then utilize the 35 items which are considered as valid, reliable, and moderately difficult to measure their students’ reading achievement.